Trust as the Foundation of the Spirituality of Mercy according to Michael Sopocko - Kruszewska, Elżbieta (Verbum Vitae, 2022)
The aim of this article is to show that Father Michael Sopocko, in his writings, presented the virtue of trust as the basis of the spirituality of mercy. This author, now blessed of the Catholic Church, was the first to carry out the mission of extending the devotion to Divine Mercy in the form given by Jesus to Sister Faustina. He elaborated on this theologically and pastorally. One might say that he built the foundation of the spirituality of mercy of modern times. The article shows how Sopocko understood the essence of the virtue of trust and what qualities he attributed to it, as well as how he perceived the importance of this virtue in Christian life and what role he attributed to it in the devotion to Divine Mercy. The author in question grounded his analyses on the virtue of trust primarily in the Word of God, which he frequently referred to. He also referred in some of his writings to the issue of the new forms of devotion to Divine Mercy and, in their context, showed trust as the foundation of the spirituality of mercy. The article uses the method of analysing the writings of Michael Sopocko with commentaries. The result of this analysis is the conclusion that the virtue of trust is not only an indispensable element of a properly understood spirituality of mercy, without which this spirituality would be incomplete and skewed, but is in fact the basis of this spirituality and gives it its proper direction.